Tuberculosis Information System: Evaluation Approach with HOT-FIT Framework - Yeni Riza; Alva Dendy Doan; Hilda Irianty; Edy Ariyanto (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: The increase in the number of pulmonary TB cases increases the risk of illness and death, which indicates the need for TB prevention and control efforts through online recording and reporting of cases using the Tuberculosis Information System (SITB). However, there are several challenges in implementing the use of SITB, which results in delays in reporting TB cases and disrupts TB prevention and treatment efforts. Purpose: The purpose of this study was to describe the use of SITB with the HOT-FIT Framework in the UPT Puskesmas Lemo area, North Barito District, Central Kalimantan. Methods: This research applies qualitative research methods with a phenomenological approach. The study population consisted of five informants who were selected deliberately (purposive sampling), including the Head of Puskesmas, TB Program Manager, TB Program Management Assistant, General Practitioner, and Laboratory Officer. Results: The results highlight that the use of Tuberculosis Information System (SITB) applications faces a number of supporting and inhibiting factors, which eventually lead to delays in reporting. Although the availability of adequate human resources (HR) is one of the supporting factors for reporting tuberculosis (TB) cases through the SITB application, the unstable internet network and lack of facilities and infrastructure such as inadequate software are also inhibiting factors. Conclusion: Puskesmas Lemo has participated in the successful implementation of TB case recording and reporting activities using SITB, but there are several aspects that still need to be improved and followed up. Thus, the Lemo Health Center still needs regular guidance and monitoring by the Health Office in carrying out its functions.